Training effect of a stationary preprogrammed target dummy on visual response time and contest performance of karate athletes - Liu, Y. H.; Chang, S. T.; Chen, S. C.; Lim, A. Y.; Chang, C. W.; See, L. C. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Response time (RT) is crucial in karate athletes and can be trained. The aim of this study was to compare standing eye-hand RT and contest performance in nonelite karate athletes who underwent 6 weeks of training using either a stationary preprogrammed target dummy (experimental group) or traditional karate instruction (control group).